META-ANALISIS: VALIDITAS DAN PRAKTIKALITAS E-MODUL MATEMATIKA PADA MASA PANDEMI COVID-19 - Siti Zulaikhah; Sandha Soemantri; Febriana Kristanti (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to analyze the level of validity and practicality of math e-modules during the Covid-19 pandemic from 2020 to 2022 using the meta-analysis method. Data was obtained by reviewing 14 scientific articles originating from Google Scholar data related to the development of mathematics e-modules during a pandemic. In the validity analysis, there were three aspects analyzed, namely content validity, presentation validity and language validity. The results of the study found that the level of validity of the mathematics e-module on the content aspect was 82.8%, the presentation aspect was 86.4%, the language aspect was 82.5%. So that the overall average validity is 83.9% in the valid category. Meanwhile, in the analysis of the practicality of the aspects analyzed, there were two aspects, namely the practicality of the teacher and the practicality of the students. The practicality level of the teacher is 86.7% and the student aspect is 85.9%. So that the overall practicality average is 86.3% in the very practical category. The results of the analysis of the validity and practicality of the mathematics e-module during the Covid-19 pandemic in the 2020 to 2022 period are valid and very practical so that they are suitable for use in the mathematics learning proces